Material Properties of Composite Materials for FSAE Car Body Panels - Azmeel Borhan, Muhamad; Intan Suraya Murat, Bibi (International Journal of Engineering and Technology, 2018)
This paper presents the mechanical properties of selected composite materials for Formula Society of Automotive Engineers (FSAE) race car body panels. The objective is to present the best materials to be used as the body panels. Kevlar, Carbon and glass fibers were fabricated as specimens and underwent some mechanical tests to determine their tensile properties, fracture toughness and impact resistance. Results from the experimental works reveal that woven Carbon fiber scored the highest in two out of three tests (tensile and fracture properties), but has the lowest impact energy that is due to its lower density compared to the other two composite materials. On the other hand, the woven Kevlar fiber consistently showed a moderate result in all three tests, and the woven glass fibers only showed a better result in impact test. Considering all these results, the woven Kevlar fiber is chosen as the best materials to be used as the FSAE carâ€™s body panels, which is based on a trade-off between strength of the materials, fracture, weight, and impact resistance. The findings may be useful for the future design, fabrication and performance of the FSAE race cars.Â Â